The secrets of facilitation the SMART guide to getting results with groups - Wilkinson, Michael (San Francisco Jossey-Bass, 2012)
The revised edition of this facilitation classic offers a wealth of targeted techniques for facilitators who seek effective, consistent, and repeatable results. Based on Michael Wilkinson's proven SMART (Structured Meeting And Relating Techniques) approach, The Secrets of Facilitation can help to achieve stellar results when managing, presenting, teaching, planning, and selling, as well as other professional and personal situations.
Includes bibliographical references and index.
Keywords: Group facilitation --Handbooks, manuals, etc